2016
DOI: 10.1038/cddis.2016.214
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitor of apoptosis protein expression in glioblastomas and their in vitro and in vivo targeting by SMAC mimetic GDC-0152

Abstract: Glioblastomas (GBMs) are the most aggressive primary brain tumors in adult and remain a therapeutic challenge. Targeting key apoptosis regulators with the ultimate aim to restore apoptosis in tumor cells could be an interesting therapeutic strategy. The inhibitors of apoptosis proteins (IAPs) are regulators of cell death and represent attractive targets, especially because they can be antagonized by SMAC mimetics. In this study, we first investigated the expression of cIAP1, cIAP2, XIAP and ML-IAP in human GBM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 38 publications
1
43
0
Order By: Relevance
“…Anderson Cancer Center and Novartis), Phase II LCL161 adjunct to paclitaxel for triple-negative breast cancer (completed in 2014, Novartis Pharmaceuticals), Phase I LCL161 adjuct to PDR001 for colorectal, triple-negative breast cancer and (2016, ongoing Novartis Pharmaceuticals)GDC-0152XIAP, cIAP1, cIAP2 and ML-lAP [100, 101]Breast cancer [100], glioblastoma [101]No informationPhase 1 solid cancers (completed in 2010, Genetech)BIRINAPANTDegradation of cIAP1 and cIAP2 [102]Breast cancer [103], ovarian cancer [104], solid tumours [105], melanoma [106]Carboplatin [104], TRAIL [102, 103], TNF-α [106]Phase II ovarian cancer, single agent (completed 2015, National Cancer Institute), Phase I lymphoma, dose escalation study (completed 2013, TetraLogic Pharmaceuticals), Phase Ib, ovarian and peritoneal cancer, Birinapant adjunct to conatumumab (Completed 2015, TatraLogic Pharmaceuticals), Phase Ib/2a, myelodysplastic syndrome, birinapant adjuct to 5-azacitidine (completed 2015, TetraLogic Pharmaceuticals), Phase II, advanced or recurrent high grade carcinoma, birinipant adjuct to platinum based agents (initiated 2017, Jonsson Comprehensive Cancer Center and TetraLogic Pharmaceuticals). Phase I/II, solid tumors, dose escalation study in combination with pembrolizumab (initiated 2017, TetraLogic Pharmaceuticals)HGS-1029XIAP inhibition, loss of cIAP expression [111]Advanced solid tumors (including colon, andrenocarcinoma) (TetraLogic Pharmaceuticals)No informationPhase I, single agent for solid tumors (completed in 2012, Aegera Therapeutics)BV6XIAP, cIAP1 and cIAP2 [107, 108]Breast cancer [112], acute myeloid leukemia (AML) [107], childhood ALL [108]Drozitumab [112], 5-azacytidine [107], dexamethasone [108]N/A …”
Section: Inhibitors Of Apoptosis (Iaps)mentioning
confidence: 99%
“…Anderson Cancer Center and Novartis), Phase II LCL161 adjunct to paclitaxel for triple-negative breast cancer (completed in 2014, Novartis Pharmaceuticals), Phase I LCL161 adjuct to PDR001 for colorectal, triple-negative breast cancer and (2016, ongoing Novartis Pharmaceuticals)GDC-0152XIAP, cIAP1, cIAP2 and ML-lAP [100, 101]Breast cancer [100], glioblastoma [101]No informationPhase 1 solid cancers (completed in 2010, Genetech)BIRINAPANTDegradation of cIAP1 and cIAP2 [102]Breast cancer [103], ovarian cancer [104], solid tumours [105], melanoma [106]Carboplatin [104], TRAIL [102, 103], TNF-α [106]Phase II ovarian cancer, single agent (completed 2015, National Cancer Institute), Phase I lymphoma, dose escalation study (completed 2013, TetraLogic Pharmaceuticals), Phase Ib, ovarian and peritoneal cancer, Birinapant adjunct to conatumumab (Completed 2015, TatraLogic Pharmaceuticals), Phase Ib/2a, myelodysplastic syndrome, birinapant adjuct to 5-azacitidine (completed 2015, TetraLogic Pharmaceuticals), Phase II, advanced or recurrent high grade carcinoma, birinipant adjuct to platinum based agents (initiated 2017, Jonsson Comprehensive Cancer Center and TetraLogic Pharmaceuticals). Phase I/II, solid tumors, dose escalation study in combination with pembrolizumab (initiated 2017, TetraLogic Pharmaceuticals)HGS-1029XIAP inhibition, loss of cIAP expression [111]Advanced solid tumors (including colon, andrenocarcinoma) (TetraLogic Pharmaceuticals)No informationPhase I, single agent for solid tumors (completed in 2012, Aegera Therapeutics)BV6XIAP, cIAP1 and cIAP2 [107, 108]Breast cancer [112], acute myeloid leukemia (AML) [107], childhood ALL [108]Drozitumab [112], 5-azacytidine [107], dexamethasone [108]N/A …”
Section: Inhibitors Of Apoptosis (Iaps)mentioning
confidence: 99%
“…Glioma is one of the most prevalent intracranial malignancies and characterized as invasive growth without obvious boundaries distinguishing from adjacent brain tumour tissues . Despite the significantly enhanced diagnosis and therapy for glioma including excision, radiation therapy and chemical therapy, the prognosis of glioma remains unfavourable because of its cell proliferation and invasion into the adjacent normal brain parenchyma .…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study we evaluated the prognostic value of the expression of cIAP1, cIAP2, XIAP and ML-IAP in human GBs and found that ML-IAP was correlated with the worst prognosis (Tchoghandjian et al, 2016). We used Smac mimetic GDC-0152 which antagonizes cIAP1, cIAP2, XIAP and also ML-IAP (Flygare et al, 2012) to test for its anti-tumoral activity in GBs.…”
Section: Introductionmentioning
confidence: 99%
“…We used Smac mimetic GDC-0152 which antagonizes cIAP1, cIAP2, XIAP and also ML-IAP (Flygare et al, 2012) to test for its anti-tumoral activity in GBs. GDC-0152 treatment increased survival of mice xenografted with U87-MG GB cells while cultured GB stem-like cells were more resistant to GDC-0152-induced cell death (Tchoghandjian et al, 2016). We then explored whether IAPs affect GB stem-like cells differently depending on oxygen levels as hypoxia has been shown to modulate drug efficacy and IAPs expression (Dong et al, 2001;Yang et al, 2014;Hsieh et al, 2015).…”
Section: Introductionmentioning
confidence: 99%